Ancient DNA resolves identity and phylogeny of New Zealand's extinct and living quail (Coturnix sp.). - Seabrook-Davison M; Huynen L; Lambert DM; Brunton DH (PUBLIC LIBRARY SCIENCE, 2009)
BACKGROUND: The New Zealand quail, Coturnix novaezealandiae, was widespread throughout New Zealand until its rapid extinction in the 1870's. To date, confusion continues to exist concerning the identity of C. novaezealandiae and its phylogenetic relationship to Coturnix species in neighbouring Australia, two of which, C. ypsilophora and C. pectoralis, were introduced into New Zealand as game birds. The Australian brown quail, C. ypsilophora, was the only species thought to establish with current populations distributed mainly in the northern part of the North Island of New Zealand. Owing to the similarities between C. ypsilophora, C. pectoralis, and C. novaezealandiae, uncertainty has arisen over whether the New Zealand quail is indeed extinct, with suggestions that remnant populations of C. novaezealandiae may have survived on offshore islands. METHODOLOGY/PRINCIPAL FINDINGS: Using fresh and historical samples of Coturnix sp. from New Zealand and Australia, DNA analysis of selected mitochondrial regions was carried out to determine phylogenetic relationships and species status. Results show that Coturnix sp. specimens from the New Zealand mainland and offshore island Tiritiri Matangi are not the New Zealand quail but are genetically identical to C. ypsilophora from Australia and can be classified as the same species. Furthermore, cytochrome b and COI barcoding analysis of the New Zealand quail and Australia's C. pectoralis, often confused in museum collections, show that they are indeed separate species that diverged approximately 5 million years ago (mya). Gross morphological analysis of these birds suggests a parallel loss of sustained flight with very little change in other phenotypic characters such as plumage or skeletal structure. CONCLUSION/SIGNIFICANCE: Ancient DNA has proved invaluable for the detailed analysis and identification of extinct and morphologically cryptic taxa such as that of quail and can provide insights into the timing of evolutionary changes that influence morphology.
Funding: This project was supported by a Massey University Vice Chancellor Doctoral Scholarship; research funding from the Supporters of Tiritiri Matangi; and a research grant from the Institute of Natural Resources, Massey University. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.
Keywords: New Zealand quail; Coturnix; Australian brown quail; DNA; Fields of Research::270000 Biological Sciences::270200 Genetics::270299 Genetics not elsewhere classified